CAD models from medical images using LAR. Issue 6 (1st November 2016) - Paoluzzi, Alberto; DiCarlo, Antonio; Furiani, Francesco; Jiřík, Miroslav
ABSTRACT: This paper points out the main design goals of a novel representation scheme of geometric-topological data, named Linear Algebraic Representation (LAR), characterized by a wide domain, encompassing 2D and 3D meshes, manifold and non-manifold geometric and solid models, and high-resolution 3D images. To demonstrate its simplicity and effectiveness for dealing with huge amounts of geometric data, we apply LAR to the extraction of a clean solid model of the hepatic portal vein subsystem from micro-CT scans of a pig liver. GRAPHICAL ABSTRACT: